Strategies to Increase Customer Trust Through Digital Service Innovation at PT Insurance Bumida Medan Branch - Tri Suci Irawan; Imsar; Nursantri Yanti (Danadyaksa: Post Modern Economy Journal, 2026)
The digital transformation within the insurance industry demands that companies not only adopt technology but also ensure the cultivation of customer trust in digital-based service systems. In this context, this study aims to analyze the strategies for enhancing customer trust through digital service innovation at PT Asuransi Umum Bumida 1967 Medan Branch using the framework of the Diffusion of Innovation Theory. This study employs a descriptive qualitative approach, collecting data through observation, in-depth interviews with staff and customers, and documentation. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana, which includes data reduction, data display, and conclusion drawing/verification. The results show that digital service innovations such as the Replay application, e-policies, and policy barcodes offer relative advantages in improving operational efficiency, service speed, and information transparency. However, the innovation adoption process is still influenced by factors such as usage complexity, varying levels of digital literacy, and the preference of some customers for manual systems. Interpersonal communication strategies through marketing, the implementation of a hybrid system, and continuous assistance have proven effective in accelerating the diffusion of innovation. It is concluded that the success of digital service innovation in building customer trust requires the integration of strengthening innovation attributes, optimizing communication, gradual adaptation, and consistent, sustainable support from the organization's social system.